Charting the Development of Multimodality in English Language Teaching within Higher Education: A Bibliometric Perspective - Zaky Dzulhiza Hawin Amalia; Heppy Mutammimah; Ummy Khoirunisya’ Masyhudianti (Universitas Islam Negeri Palopo, 2025)
Multimodality has become a crucial component of 21st-century learning as students increasingly engage with diverse modes of communication in their daily lives. While multimodality has been widely studied, limited attention has been given to its development in English Language Teaching (ELT) within higher education. This study fills that gap by mapping global research trends, leading contributors, and thematic directions through a bibliometric analysis using the Scopus database. A total of 265 documents were initially retrieved, and 184 English-language journal articles published between 2015 and 2024 were included for analysis. Data were processed using VOSviewer to visualize keyword co-occurrence and identify emerging research clusters. The findings reveal that China is the most productive country with 58 publications, followed by the United States with 23, and that National Yunlin University of Science and Technology is the leading institutional contributor. Six thematic clusters were identified, covering multimodality, discourse analysis, digital storytelling, and teacher education. These insights provide a comprehensive overview of the field’s evolution and offer practical implications for educators and researchers aiming to enhance multimodality and pedagogical innovation within higher education.